Mesenchymal Stem/Stromal Cells in Organ Transplantation - Dayanand Deo; Misty Marchioni; Prakash Rao (MDPI AG, 2022)
Organ transplantation is essential and crucial for saving and enhancing the lives of individuals suffering from end-stage organ failure. Major challenges in the medical field include the shortage of organ donors, high rates of organ rejection, and long wait times. To address the current limitations and shortcomings, cellular therapy approaches have been developed using mesenchymal stem/stromal cells (MSC). MSC have been isolated from various sources, have the ability to differentiate to important cell lineages, have anti-inflammatory and immunomodulatory properties, allow immunosuppressive drug minimization, and induce immune tolerance towards the transplanted organ. Additionally, rapid advances in the fields of tissue engineering and regenerative medicine have emerged that focus on either generating new organs and organ sources or maximizing the availability of existing organs. This review gives an overview of the various properties of MSC that have enabled its use as a cellular therapy for organ preservation and transplant. We also highlight emerging fields of tissue engineering and regenerative medicine along with their multiple sub-disciplines, underlining recent advances, widespread clinical applications, and potential impact on the future of tissue and organ transplantation.